THE EFFECT OF TEACHER TEACHING VARIATIONS AND STUDENTS' ATTENTION TO LEARNING OUTCOMES IN ISLAMIC EDUCATION SUBJECTS - Hayatil Husnah; Martin Kustati; Rehani - (Postgraduate Studies UIN Sulthan Thaha Saifuddin Jambi, 2022)
The purpose of this study was to obtain data so that it is known the effect of variations in teacher teaching on learning outcomes, student attention to learning outcomes, and variations in teacher teaching and student attention together on learning outcomes in Islamic Education (PAI) subjects. This type of research is quantitative using associative descriptive method. The population in this study were all students at SMPN Bayang District as many as 1050 students. The sampling technique is Proportional Startified Random Sampling, in order to obtain a sample of 91 students. Data collection techniques through questionnaires and documentation studies. Processing data by testing requirements analysis and hypothesis testing. The research result shows that there is a significant effect in teacher teaching variations towards study result, students’ attention towards study result, and there is a significant effect between teacher teaching variations and students’ attention altogether in Islamic Education subject. Abstrak: Tujuan penelitian ini adalah untuk memperoleh data sehingga diketahui pengaruh variasi mengajar guru terhadap hasil belajar, perhatian peserta didik terhadap hasil belajar, dan variasi mengajar guru dan perhatian peserta didik secara bersama-sama terhadap hasil belajar pada mata pelajaran Pendidikan Agama Islam (PAI). Jenis penelitian ini adalah kuantitatif dengan menggunakan metode deskriptif asosiatif. Populasi dalam penelitian ini adalah seluruh peserta didik di SMPN Se Kecamatan Bayang sebanyak 1050 peserta didik. Teknik pengambilan sampel yaitu Proportional Startified Random Sampling, sehingga diperoleh sampel 91 orang peserta didik. Teknik pengumpulan data melalui angket dan studi dokumentasi. Pengolahan data dengan cara uji persyaratan analisis dan uji hipotesis. Hasil penelitian mengungkapkan bahwa terdapat pengaruh yang signifikan variasi mengajar guru terhadap hasil belajar, perhatian peserta didik terhadap hasil belajar, dan terdapat pengaruh yang signifikan antara variasi mengajar guru dan perhatian peserta didik secara bersama-sama pada mata pelajaran Pendidikan Agama Islam. Kata-kata kunci: variasi mengajar guru, perhatian peserta didik, hadil belajar